Using a Video Project to Enhance Students’ Speaking Ability - Zein, T. Thyrhaya; Sofyan, Rudy; Tarigan, Bahagia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Speaking is a skill often considered the benchmark of student’s success in learning English. Many studies have been conducted to examine the approaches, methods, and media that work best in improving the students’ speaking ability. One of the methods that can be used in teaching speaking is making a video project. This paper aims to find out how using a video project enhances the students’ speaking ability. This study was conducted using a descriptive method, taking the students at senior high schools in Medan as the participants. The data were collected using an observation method. The data were analyzed to show how a video project was used in teaching speaking and how it enhances the students’ speaking ability. The results indicate that using a video project in teaching speaking motivates the students to show their best speaking performance, eliminates their shyness and inhibition in speaking, and improves the students’ speaking fluency in English. Thus, the results recommend the use of a video project as a good method in teaching speaking English to senior high school students.